The terrestrial flatworm Microplana scharffi (Geoplanidae, Microplaninae): mitochondrial genome, phylogenetic proximity to the Bipaliinae and genes related to regeneration - Gastineau, Romain; Murchie, Archie K.; Gey, Delphine; Winsor, Leigh; Justine, Jean-Lou (Zootaxa, 2024)
A genome skimming approach of sequencing was undertaken on a subfamily of terrestrial flatworms that had been neglected in genomic studies until now, namely the Microplaninae as represented here by Microplana scharffi. A single run of short-read sequencing enabled retrieval of the complete mitogenome, the two paralogous versions of the 18S gene, the elongation factor gene EF1α, plus two genes involved in the regeneration process, namely those coding for ß-CATENIN-1 and adenomatous polyposis coli (APC). The 15,297 bp mitogenome lacks a functional tRNA-Ala and has a mandatory alternative TTG start codon in its cox1 gene. The multiprotein phylogeny, inferred from mitogenome proteins, positions M. scharffi as sister-group to the Bipaliinae with maximum support, although the organisation of the mitogenomes shows features previously never observed among Bipaliinae, such as the conserved 32 bp overlap between ND4 and ND4L. Similarly to what has been observed in recent publications on other species of Geoplanidae, the two types of 18S genes display strongly different coverages and are only 90.57% identical. Additionally, alien DNA was identified in the pool of contigs in the form of the complete mitochondrial genome of Lumbricus rubellus, confirming previous observations on the feeding habits of M. scharffi.